Outcome of Elastic Stable Intramedullary Nail in Length Unstable Diaphyseal Femur Fractures in Children: A Case Series - Bhandari, Prawesh S; Uprety, Suresh (Journal of Institute of Medicine Nepal, 2020)
Introduction Elastic stable intramedullary nailing (ESIN) has been a common method of treatment of diaphyseal femur fracture in children. Though they are used in length stable fracture with favourable results, their use is debated in case of length unstable variants. The objective of the study was to evaluate outcome of these nails in length unstable diaphyseal femur fracture in children.MethodsWe retrospectively reviewed seven fractures in seven children treated with ESIN for functional outcome.ResultsTotal of seven patients with seven unstable femur fractures were studied. There was male predominance with 71.4%. The fracture united at a mean duration of 12 wks. The overall Flynn scoring showed 71.4 % excellent and 28.6 % satisfactory result.ConclusionElastic stable intramedullary nailing can be safely used in length unstable variant of femur fracture in children.